Exploring the Dimensions of Academic Human Capital: Insights into Enhancing Higher Education Environments in Egypt - Manuel Sousa Pereira; António Cardoso; Nourhan M. El Sherbiny; Amândio F. C. da Silva; Jorge Figueiredo; Isabel Oliveira (Social Sciences)
The performance of higher education institutions is significantly influenced by their academic human capital (AHC), which encompasses research competencies, dynamic capacity, working capacity, critical thinking, social capital, and external relations. This study aims to investigate the interrelationships among these dimensions and their collective impact on institutional performance. Utilizing a comprehensive literature review and empirical analysis, we identify key factors that enhance AHC and propose strategies for optimizing these dimensions to foster innovation, adaptability, and organizational effectiveness. The quantitative study with a descriptive design uses a questionnaire, collecting 302 responses from university professors and researchers in Egypt. The findings highlight the pivotal role of research competencies and dynamic capacity in driving academic excellence and institutional resilience. Additionally, the study underscores the importance of external relations and social capital in enriching academic environments and facilitating knowledge transfer. By providing a nuanced understanding of AHC, this research offers actionable insights for policymakers and educational leaders aiming to bolster the performance and sustainability of higher education institutions.